The effects of oral birth control pills (contraceptive pills) intake on lyophilized saliva and its oral manifestations - Rasheed, Rafil Hameed; Faisal Ahmed, Rehab (Bionatura, 2023)
A woman is susceptible to oral diseases at various stages in her life span. Besides, multiple biological, behavioral, and social factors affect the general health condition. Many drugs or chemicals can influence the oral cavity & associated structures. An example of these drugs group is oral contraceptive pills (OCS) which women widely use to prevent pregnancy and determine the number of children, and hormonal therapy. This study aims to evaluate the effect of oral contraceptive pills use on salivary secretion and composition in addition to the occurrence of any oral manifestations with the uses of these drugs among women aged 16-45 years. The total number of sample subjects is 51 women. The samples were separated into two groups: The first group included 21 unmarried women with no previous experience with oral contraceptive pills (control group). In contrast, the second group consisted of 30 women who were married and using this drug (study group). This study is considered to be a comparative study between these two groups concerning the analysis of the salivary composition, unstimulated salivary flow rates and PH level: The results obtained from this study showed a marked significant difference in salivary analysis between the drug user & nonuser drug groups concerning the salivary flow rate while the PH had no statistical differences between them. However, the two groups had a significant difference in alkaline phosphatase enzyme. The salivary analysis showed highly substantial variations in immunoglobulin A (IgA) & total protein levels in saliva between control & study groups; also, in this study, there was a positive association between gingival inflammation with gingival index score (2) (80%), gingival index score (3) (100%) and duration for taking the drug. By this drug administration, the altered salivary flow rate & levels of salivary contents that include (secretary proteins, IgA and enzymes) may influence and play an essential role in oral & dental health. Keywords: saliva; oral health; oral contraceptive pills.